Examining demographic characteristics and food access indicators from the location of vegan soul food restaurants in the south. Issue 2 (17th February 2022) - Crimarco, Anthony; Turner-McGrievy, Gabrielle M.; Adams, Swann; Macauda, Mark; Blake, Christine; Younginer, Nicholas
ABSTRACT: Objective: There have been a number of soul food restaurants serving exclusively vegan meals opening up across the country to appeal to African Americans and others interested in eating healthier soul foods. This study determined the number of restaurants serving vegan soul foods in the South and identified the locations of these restaurants in order to understand the characteristics of the surrounding communities that they serve. Design: Two reviewers identified restaurants using standardized search criteria for menu items in the 16 states (and the District of Columbia) that are categorized as being in the South from the Census Bureau. Mean percentage of African Americans, poverty rates, and obesity rates by county where restaurants were located were collected via census data. Restaurants were classified as being in or out of a food desert zone using the United States Department of Agriculture's (USDA) food atlas map (0.5- and 1.0-mile radius). T-tests were conducted to test for differences in the census data between the restaurants that were considered to be in and out of a food desert zone. Results: Overall, 45 restaurants met the inclusion criteria. Counties where restaurants were located had a mean African American population of 36.5 ± 18.5%, mean poverty rate of 15.5 ± 3.85% and mean obesity rate of 26.8 ± 4.8%. More than one third ( n = 18, 40.0%) of the restaurants were considered to be in a food desert zone. There were no significant differences in the mean population, obesity, and poverty rates between restaurants classified in a food desert zone and restaurants not located in a food desert zone. Conclusion: A significant number of restaurants were classified in food desert zones, implying their potential to provide healthier meals by serving vegan soul foods to residents in the surrounding neighborhoods. Future work should assess how these restaurants might influence healthier eating habits in their communities.